Six-Sigma to operational excellence: role of tools and techniques. (15th November 2004) - Basu, Ron
This paper covers the concept of quality and quality management. Quality has three dimensions – product quality, process quality and organisation quality. The cost of quality can be measured in terms of prevention cost, appraisal cost, internal failure cost and external failure cost. Quality Management has evolved over the years from inspection to control to assurance to TQM. The new waves of Six-Sigma, Lean Processes and FIT SIGMA are embedded in the holistic programmes of Operational Excellence. We need both tools and techniques in quality management and operational excellence programmes. We have reviewed both the positive drivers and the problems conducive to restraining forces for the use and application of tools and techniques. We have concluded that success factors are derived from the resultant vector of the mutually contradicting driving forces and restraining forces. The critical success factors are: top management commitment, availability of resources, well designed education and training programmes for appropriate tools and techniques, and a rigorous project management approach.